2010
DOI: 10.1002/ange.201000094
|View full text |Cite
|
Sign up to set email alerts
|

Open Metal Sites within Isostructural Metal–Organic Frameworks for Differential Recognition of Acetylene and Extraordinarily High Acetylene Storage Capacity at Room Temperature

Abstract: Open metal sites have played very important roles in synthetic assemblies and biological systems because of their specific recognition of small molecules and thus for their highly selective molecular transformations, transport, and storage. [1][2][3][4] Understanding the molecular recognition between the open metal sites and the substrate molecules at the molecular level will not only facilitate the discoveries of new catalysts, sensing, and storage materials, but will also provide a deep insight in the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 63 publications
4
46
0
Order By: Relevance
“…As then, design and synthesis of high‐performance MOFs has become an increasingly hot research topic in the field of C 2 H 2 storage. Considering the compression limit of C 2 H 2 , one strategy commonly adopted to enhance guest‐host interactions is introducing open metal sites (OMS) into MOFs . Among such subset of MOFs, immobilization of open Cu sites using the secondary building unit (SBU) of dicopper paddle‐wheel Cu 2 (COO) 4 was found to be an effective approach .…”
Section: Introductionmentioning
confidence: 99%
“…As then, design and synthesis of high‐performance MOFs has become an increasingly hot research topic in the field of C 2 H 2 storage. Considering the compression limit of C 2 H 2 , one strategy commonly adopted to enhance guest‐host interactions is introducing open metal sites (OMS) into MOFs . Among such subset of MOFs, immobilization of open Cu sites using the secondary building unit (SBU) of dicopper paddle‐wheel Cu 2 (COO) 4 was found to be an effective approach .…”
Section: Introductionmentioning
confidence: 99%
“…In order to design new MOFs with improved properties, it is of critical importance to understand the nature of the interaction between the absorbed molecule and the MOF host. Such understanding can either be gained through theory, using first-principles simulations, [8][9][10][11][12][13][14][15][16][17][18] or through experimental probes, such as infrared (IR) absorption and Raman scattering. [8][9][10][11]18,[20][21][22][23][24] Much progress has been made in improving the properties of MOFs.…”
mentioning
confidence: 99%
“…For example, it has been shown that using unsaturated metal centers, such as MOF74 with open Mg, Mn, Zn, Ni, Cu, or HKUST-1 with Cu, results in higher absorption density for hydrogen and faster absorption at small partial CO 2 pressures, the latter of which is highly desirable for CO 2 capturing applications. [5][6][7][8][9][14][15][16][17][19][20][21][22] It has further been shown that iso-structural MOFs with different open metal centers can have very different absorption rates at low pressure. 7 In particular, the electronically similar metal centers Mg and Zn result in a much faster CO 2 uptake rate in Mg-MOF74 than in Zn-MOF74 at a pressure smaller than 0.1 atm.…”
mentioning
confidence: 99%
“…Metal-organic frameworks (MOFs), assembled by inorganic vertices (metal ions or clusters) and organic linkers, have attracted extensive research interest because of their diverse structural topologies, tunable functionalities, as well as versatile applications in catalysis [40][41][42][43], biomedical imaging [44,45], gas separation and storage [46][47][48]. Moreover, inspired by their high surface areas, porosity, and abundant carboncontaining linkers, MOFs have been demonstrated as promising templates or precursors to fabricate nanostructured materials via thermolysis [49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%